2020
DOI: 10.2147/ijgm.s267446
|View full text |Cite
|
Sign up to set email alerts
|

<p>Violence Against Healthcare Workers at Primary Care Centers in Dammam and Al Khobar, Eastern Province, Saudi Arabia, 2019</p>

Abstract: Workplace violence is common throughout the world. It causes many serious problems in the healthcare sector, where it significantly impacts healthcare workers, the services provided, and organizations as a whole. However, few studies have investigated these issues in Saudi Arabia. This study examined the prevalence of violence against healthcare workers at primary care centers in Dammam and Al Khobar, in the Eastern Province of Saudi Arabia. The study also assessed the types, perpetrators, perceived causes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…Their presence in stressful situations such as deaths, waiting to visit a physician, hospital overcrowding, repeated requests by patients and their relatives for special privileges can lead to illogical and tense reactions situations between nurses, other health professionals, and patients. Previous studies agree with the above findings, stating that nurses are most exposed to verbal, emotional, physical, and even sexual abuse [22,23]. On the other hand, physicians enjoy more respect from patients and other colleagues, due to patients' asymmetric access to information and fear for good care.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Their presence in stressful situations such as deaths, waiting to visit a physician, hospital overcrowding, repeated requests by patients and their relatives for special privileges can lead to illogical and tense reactions situations between nurses, other health professionals, and patients. Previous studies agree with the above findings, stating that nurses are most exposed to verbal, emotional, physical, and even sexual abuse [22,23]. On the other hand, physicians enjoy more respect from patients and other colleagues, due to patients' asymmetric access to information and fear for good care.…”
Section: Discussionsupporting
confidence: 78%
“…Giving that verbal abuse by colleagues or patients is a reality in the health care environment [22,23], the purpose of this study was to investigate the prevalence of verbal violence in the operating room at three general hospitals in the Peloponnese region of Greece.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of workplace violence (WPV) against health workers; mainly in hospitals 8 but also in primary care health services. 9 This is not an uncommon phenomenon, as shown by Liu et al 10 Violence against health workers is a complex problem, the motivations of which must be evaluated carefully. Some studies agree that the lack of punishment to the perpetrator and the lack of reporting procedures and policies are major factors.…”
mentioning
confidence: 99%
“…Some studies agree that the lack of punishment to the perpetrator and the lack of reporting procedures and policies are major factors. 9 , 11 Overcrowding 9 and lack of understanding between patients and health personnel 12 , 13 have also been suggested as triggers.…”
mentioning
confidence: 99%
“…Previous literature showed that, WPV is a prevalent problem among HCPs worldwide, developed as well as developing countries [ 4 7 ]. Previous literature showed that, WPV is a prevalent problem among HCPs in Arab countries as well [ 8 12 ]. In Egypt, previous studies showed that WPV is a major problem against HCPs in hospitals [ 13 – 17 ].…”
Section: Introductionmentioning
confidence: 99%